Controle da Plutella xylostella L. 1758 e entomofauna associada a cultura da couve na área de transição Cerrado-Amazônia - Gemelli, Arthur Yoshio (2020)
The cruciferous moth is one of the main pests that attacks as crops of cabbage, broccoli, cauliflower and kale (Brassica oleracea L. Brassicales: Brassicaceae). The present work had as objective to make a diagnosis of the practices of control of cruciferous moths adopted by the family farmers that cultivate cabbage and, to know an entomofauna present in this culture. For this, the following methods were used: semi-structured, snowball selection and survey of entomofauna associated with cabbage cultivation. 42 farmers were interviewed, who produced and sold cabbage, obtaining answers about their social profile, production of cabbage, handling of cruciferous traits, use of individual protection equipment, commercialization and ethno- knowledge. In addition, in 10 producers in Lucas do Rio Verde, there was an installation of adhesive traps, in order to identify the insects, present in the crop, for 12 months. The interviewees are mostly male, have a low level of education, are married or cohabited, have their origins in the south and southeast of Brazil and are over 41 years old. In moth control, farmers use products without registration for the crop, or they can cause poisoning and affect the health of the final consumer of their products. Related to ethno-knowledge, farmers acquired experience, developed or passed the years methods that help in the control of cruciferous traits, such as: Sequential collections, tanned and cassava peels for three days and use; do not stick the same plot and use silicon to stiffen like leaves. With an assessment of the entomofauna associated with cabbage cultivation, 64,325 insects were identified at the family level, distributed in 52 families and 11 licenses. The families with the largest number of specimens were Ceratopogonidae (Diptera), Cicadellidae (Hemiptera: Auchernorryncha) and Aleyrodidae (Hemiptera: Sternorryncha). It was possible to identify five pest insects for cabbage (Plutella xylostella L, Ascia monuste orseis, Diabrótica speciosa, Bemisia sp., Agrotis ipsilon), five families of parasitoid insects (Chalcididae, Ichneumonidae, Braconidae, Pteromalidae and Diapriidae) and 12 families of insect’s predators. Two main insect guilds have been identified: predators and cabbage pests. The knowledge of the entomofauna associated with the cultivation of cabbage makes it possible to know the insects present in their crops, whether pests or not, or which can assist in the management of the crop and the pests, decreasing according to the evaluation and, consequently, the benefit or profit.